El Indio - Coching, Francisco V. (Quezon City Vibal Foundation, 2009)
"Chronicles the adventures of the young mestizo Fernando, who returns to the Philippines from Spain in search of his missing father. First serialized in Pilipino komiks in 1953"--P. [4] of cover.
Originally published in Pilipino komiks by Atlas Publishing in 1953.
Keywords: Comics, books, strips, etc. -- Philippines; Graphic novels -- Philippines